Penelusuran Informasi pada Pemustaka Universitas Negeri Padang - Malta Nelisa; Ardoni Ardoni (Institut Agama Islam Negeri Salatiga, 2018)
Information search is important in supporting the activity of “Tri Dharma PerguruanTinggi”. Student information search results are often found to be very similar to statementsin the reference used. Skills in the use of information reflect the understandingof college librarians against information literacy. The research method used in compilingthis article is by qualitative research. In this research used information tracingmodel with stages namely: starting, chaining, browsing, differentiating, monitoring,extracting, verifying, and ending. The study was conducted on 143 users from StateUniversity of Padang (UNP) and University of Andalas (Unand). The results showedthat the lecturer is an important source of information for the user to know the initialreference that will be used in the completion of academic tasks. In addition, collegelibrarians have a high dependence on internet resources. In terms of the formulationof information retrieval results, some readers use the full statement in reference. Inother words, the user does not formulate the search results according to his or herunderstanding. However, some others